Oral administration of Pinus koraiensis cone essential oil reduces rumen methane emission by altering the rumen microbial composition and functions in Korean native goat (Capra hircus coreanae) - Choi, Youyoung; Lee, Shin Ja; Kim, Hyun Sang; Eom, Jun Sik; Jo, Seong Uk; Guan, Le Luo; Seo, Jakyeom; Park, Tansol; Lee, Yookyung; Lee, Sang Suk; Lee, Sung Sill (Frontiers in Veterinary Science, 2023)
This study aimed to investigate Pinus koraiensis cone essential oil (PEO) as a methane (CH4) inhibitor and determine its impact on the taxonomic and functional characteristics of the rumen microbiota in goat. Ten growing Korean native goats (Capra hircus coreanae, 29.9±1.58 kg, male) were assigned to different dietary treatments; control (CON; basal diet without additive) and PEO (basal diet + 1 g/d of PEO) by a 2  2 crossover design. Methane measurements were conducted every 4 consecutive days for 17–20 days using a laser CH4 detector. Samples of rumen fluid and feces were collected during each experimental period to evaluate the biological effects and dry matter (DM) digestibility after PEO oral administration. The rumen microbiota was analyzed via 16S rRNA gene amplicon sequencing. The PEO oral administration resulted in reduced CH4 emission (eructation CH4/body weight0.75, P = 0.079) without affecting DM intake; however, it lowered the total volatile fatty acids (P = 0.041), molar proportion of propionate (P = 0.075), and ammonia nitrogen (P = 0.087) in the rumen. Blood metabolites (i.e., albumin, creatinine, and triglyceride) were significantly affected (P < 0.05) by PEO oral administration. The absolute fungal abundance (P = 0.009) was reduced by PEO oral administration, whereas ciliate protozoa, total bacteria, and methanogen abundance were not affected. The composition of rumen prokaryotic microbiota was altered by PEO oral administration with lower evenness (P = 0.054) observed for the PEO group than the CON group. Moreover, PICRUSt2 analysis revealed that the metabolic pathways of prokaryotic bacteria, such as pyruvate metabolism, was enriched in the PEO group. We also identified the Rikenellaceae RC9 gut group as the taxa potentially contributing to the enriched KEGG modules for histidine biosynthesis and pyruvate oxidation in the rumen of the PEO group using FishTaco analysis. The entire co-occurrence networks showed that more nodes and edges were detected in the PEO group. Overall, these findings provide an understanding of how PEO oral administration affects CH4 emission and rumen prokaryotic microbiota composition and function. This study may help develop potential manipulation strategies to find new essential oils to mitigate enteric CH4 emissions from ruminants